Assessment of satisfaction level of the occupants of green building case study: Green Tech, Bandar Baru Bangi, Selangor / Mohd Shakimi Md Yusoff - Md Yusoff, Mohd Shakimi (2010)
A Green Building where are design and construction of buildings using methods and elements that are resource efficient and that will not compromise the health of the environment or the associated health and well-being of the building's occupants, construction workers, the general public, or future generations and the low cost of building maintenance where to upkeep the condition and the price for bills of electricity and water. Green building involves the consideration of many issues, including price of construction, site impacts, indoor environment, energy and water use, and lifecycle impacts of building materials. In this thesis, the performances of the green building from the occupant prospective are discussed. Empirical data, along with information from secondary sources are then presented regarding the barriers to more widespread elements of green building as well as public and private collaborative efforts, which have been or might be effective in lowering the primary barriers. The data presented in this thesis are mainly derived from responses to a questionnaire that was developed for this research project. The questionnaire was completed by architects, engineers, maintenance, workers, public and consultants who have an involvement in occupy of the green building.